Minimising bulk lifetime degradation during the processing of interdigitated back contact silicon solar cells. (12th September 2017) - Rahman, Tasmiat; To, Alexander; Pollard, Michael E.; Grant, Nicholas E.; Colwell, Jack; Payne, David N.R.; Murphy, John D.; Bagnall, Darren M.; Hoex, Bram; Boden, Stuart A.
Abstract: In this work, we develop a fabrication process for an interdigitated back contact solar cell using BBr3 diffusion to form the p + region and POCl3 diffusion to form the n + regions. We use the industry standard technology computer‐aided design modelling package, Synopsys Sentaurus, to optimize the geometry of the device using doping profiles derived from electrochemical capacitance voltage measurements. Cells are fabricated using n ‐type float‐zone silicon substrates with an emitter fraction of 60%, with localized back surface field and contact holes. Key factors affecting cell performance are identified including the impact of e‐beam evaporation, dry etch damage, and bulk defects in the float zone silicon substrate. It is shown that a preoxidation treatment of the wafer can lead to a 2 ms improvement in bulk minority carrier lifetime at the cell level, resulting in a 4% absolute efficiency boost. Abstract : A key factor in pushing performances of interdigitated back contact solar cells lies in the quality of the bulk material and mitigating process‐induced degradation. Our results show that a preoxidation treatment of n ‐type float zone wafers can lead to >2 ms improvement in bulk minority carrier lifetime at the cell level, resulting in a 4% absolute efficiency boost.